Detrimental effects of clothianidin on foraging and dance communication in honey bees - Tison, Léa (PLoS One, 2020)
Ongoing losses of pollinators are of significant international concern because of the essential role they have in our ecosystem, agriculture, and economy. Both chemical and non-chemical stressors have been implicated as possible contributors to their decline, but the increasing use of neonicotinoid insecticides has recently emerged as particularly concerning. In this study, honey bees were exposed orally to sublethal doses of the neonicotinoid clothianidin in the field in order to assess its effects on the foraging behavior, homing success, and dance communication. The foraging span and foraging activity at the contaminated feeder decreased significantly due to chronic exposure at field-realistic concentrations. Electrostatic field of dancing bees was measured and it was revealed that the number of waggle runs, the fanning time and the number of stop signals were significantly lower in the exposed colony. No difference was found in the homing success and the flight duration between control and treated bees released at a novel location within the explored area. However, a negative effect of the ambient temperature, and an influence of the location of the trained feeder was found. Finally, the residues of clothianidin accumulated in the abdomens of exposed foraging bees over time. These results show the adverse effects of a chronic exposure to sublethal doses of clothianidin on foraging and dance communication in honey bees.